The pendulum effect of the digital transition. A qualitative investigation on media in Basque and Catalan languages - Álvarez Berastegi, Amaia; Gurrutxaga, Guillermo; Goikoetxea, Udane (Estudios sobre el Mensaje Periodístico, 2019)
This article offers an analysis of the development of digital journalism. The primary argument is that digital journalism is currently involved in a third stage in which there is a need to go back to basic journalistic principles, such as contrast and the contextualisation of the news. In the previous stage there were three main elements: the fight for being the first in giving the news, the rapid technological development and the proliferation of fake news. The current stage –the one we called the digital pendulum- is a reaction to these elements. The methodology of the study is based on the analysis of 24 semi-structured interviews with representatives of six news organisations in Catalan and Basque language (Berria, Argia and Goiena, in the Basque case, and Ara, El Punt Avui and Vilaweb, regarding Catalonia).
Keywords: Digital Journalism; Slow Journalism; History of Journalism; Fake news; Online news media